The word made strange: theology, language, culture - Milbank, John (Blackwell Publishers, 1997)
The essays in this new book from John Milbank range over the entire field of theology, and both extend and enrich the theological perspective underlying his earlier Theology and Social Theory. The essays are focused around the theme of a theological approach to language, and offer a richly textured and broad ranging inquiry which will contribute to a variety of contemporary debates